Environmental risks and the media (Rouledge, 2000)
Environmental Risks and the Media explores the ways in which environmental risks, threats and hazards are represented, transformed and contested by the media. At a time when popular conceptions of the environment as a stable, "natural" world with which humanity interferes are becoming increasingly contested, the media's methods of encouraging audiences to think about environmental risks--from the "mad cow" crisis to global warming--are becoming more and more controversial. Examining large-scale disasters as well as "everyday" hazards, the contributors consider the tensions between entertainment and information in media coverage of the environment. The issues explored include: how the media frame "expert," "counter-expert" and "lay public" definitions of environmental risk; the role played by environmental pressure groups like Greenpeace in shaping media coverage; and the media's emphasis on spectacular events at the expense of issue-sensitive reporting.